Disain Dan Uji Teknis Alat Pengering Ikan Tipe Lemari (Technical Design and Testing of Box-Type Fish Dryer) - Rizal Alamsyah; Yoeswadi -; Hadi K. Purwadaria; Tamsil Tahir (Balai Besar Industri Agro, 1986)
The disadvantage of using sun Drying are its dependance on weather, contamination of insects, unequality of the product dryness and quality, high labour and operational cost, and limitation of drying area. Mechanical dryer would lessen the above problems. This research is aimed at the making and testing of prototype of box type mechanical fish dryer of 200 kg capacity. The quality of dried product is relatively equal to commercial products. The drying condition are as follows: Temperature 40 degree-50 degree celcius, RH 40 0-50 0 %, drying air velocity 90-120 m/min. on the plenum, and temperature around the fish 29 0-36 0 C.